2014
DOI: 10.1017/s0142716413000568
|View full text |Cite
|
Sign up to set email alerts
|

Effects of transitional bilingual education on Spanish-speaking preschoolers’ literacy and language development: Year 2 results

Abstract: Year 2 findings are reported from a longitudinal, experimental-control study involving 31 Spanishspeaking preschoolers (aged 38-48 months) randomly assigned to two Head Start classrooms. In Year 1, classrooms differed only in the language of instruction, with teachers using only Spanish in one classroom and only English in the other. In Year 2, an experimental transitional bilingual education (TBE) model was implemented, with English being gradually introduced in the TBE classroom until a ratio of 30:70 Englis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 51 publications
0
8
0
1
Order By: Relevance
“…Differences in exposure to primary and secondary language and literacy environments in children’s homes and communities might contribute, beyond intervention effects, to study-reported differences in performance on English outcomes (cf. Durán et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Differences in exposure to primary and secondary language and literacy environments in children’s homes and communities might contribute, beyond intervention effects, to study-reported differences in performance on English outcomes (cf. Durán et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Because simultaneous or sequential DLL status might have an impact on children’s learning of a second language (Hammer et al, 2008), specifying this information would be helpful for interpreting study findings and should be included in future studies. More precise reporting of home language(s) exposure both before and during intervention has been recommended (Durán et al, 2015). Reporting these data would allow for more nuanced examinations of effects, including the examination of potential moderators and mediators of intervention effects.…”
Section: Discussionmentioning
confidence: 99%
“…All findings from the preschool studies indicated no significant differences in English outcomes between students in the bilingual program (i.e., in either the DLP or the TBP) and students in the EO program. In the longitudinal study by Durán et al (2015), ELs in the TBP had growth trajectories similar to those of ELs in the mainly EO program in English. In Spanish, however, ELs in the TBP maintained their Spanish advantage compared to ELs in the EO program, corroborating previous findings with ELs in the primary grades, suggesting that bilingual programs present an opportunity for ELs to maintain their L1 without a detriment to their English reading and language development.…”
Section: Selected Empirical Studies Of Bilingual Programs Published Smentioning
confidence: 81%
“…We found five studies published since 2003 that met our inclusion criteria and that compared the effectiveness of different bilingual programs (or interventions) using an RCT design, as indicated in Table 5. Of these, all but one (Slavin, Madden, Calderón, Chamberlain, & Hennessy, 2011) were conducted with students in the preschool/early elementary grades; two (Durán, Roseth, & Hoffman, 2015; Slavin et al, 2011) were longitudinal. The most common comparisons were between a mainly EO program and a DLP or a TBP.…”
Section: Selected Empirical Studies Of Bilingual Programs Published Smentioning
confidence: 99%
“…Although the normative group did not match our sample, the TVIP was selected to allow for comparison of Spanish vocabulary performance with that reported in other recent research studies focusing on Spanish-English speaking children in the United States (Barnett, Yarosz, Thomas, Jung, & Blanco, 2007; L. E. Cohen, Kramer-Vida, & Frye, 2012; Durán, Roseth, & Hoffman, 2010, 2015; Durán, Roseth, Hoffman, & Robertshaw, 2013; Leacox & Wood Jackson, 2014; Roberts, 2008).…”
Section: Methodsmentioning
confidence: 99%